2004
DOI: 10.1160/th03-04-0222
|View full text |Cite
|
Sign up to set email alerts
|

The factor V C1 domain is involved in membrane binding: identification of functionally important amino acid residues within the C1 domain of factor V using alanine scanning mutagenesis

Abstract: The contribution of the factor Va C1 domain (fVa-C1) to assembly of the prothrombinase complex has not been previously investigated. The homologous fVa-C2 domain contains a binding site for phosphatidylserine (PS) that includes the indole moieties of Trp(2063)/Trp(2064) at the apex of spike-1. In order to investigate the structure and function of fVa-C1 a molecular model was constructed based on the structure of fVa-C2. The aromatic and hydrophobic side chains of Tyr (1956) /Leu (1957) in fVa-C1 are located at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 46 publications
6
39
1
Order By: Relevance
“…We conclude that although PE does promote Va binding to membranes, PS promotes tighter binding in a PE-independent fashion. As a control, we showed that the K d for bovine Va binding to 75:25 DOPC:DOPS membranes (0.35 nM) ( Table 2) was comparable with that reported for human recombinant factor Va to synthetic vesicles (K d ϭ 0.24 nM) (28), indicating that our results are not species-specific.…”
Section: Membranesupporting
confidence: 83%
“…We conclude that although PE does promote Va binding to membranes, PS promotes tighter binding in a PE-independent fashion. As a control, we showed that the K d for bovine Va binding to 75:25 DOPC:DOPS membranes (0.35 nM) ( Table 2) was comparable with that reported for human recombinant factor Va to synthetic vesicles (K d ϭ 0.24 nM) (28), indicating that our results are not species-specific.…”
Section: Membranesupporting
confidence: 83%
“…As in FVIII, the C2 domain contains the primary membrane-binding site of FV. 31,32 The FV A3 33 and C1 34 domains also appear to interact with membranes. In FV and/or FVIII, the C domains may reorient during membrane attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the tryptophans on the C2 spikes, the tyrosines would not insert into, but rather could interact favorably with, phospholipid membranes (39,40). A very recent report using alanine-scanning mutagenesis identified these leucine and tyrosine residues on the C1-3 spike as important in prothrombinase activity (41). Additionally, two arginine residues in human factor Va (Lys-2010 and Arg-2014 in the bovine molecule) were shown to have a significant impact on function.…”
Section: Domain Interfacesmentioning
confidence: 99%